Wound closure by means of free flap and arteriovenous loop: Development of flap autonomy in the long-term follow-up - Rother, Ulrich; Müller-Mohnssen, Helena; Lang, Werner; Ludolph, Ingo; Arkudas, Andreas; Horch, Raymund E.; Regus, Susanne; Meyer, Alexander (International Wound Journal, 2019)
Free flaps in combination with arterial reconstruction by means of arteriovenous loops or bypass have, meanwhile, been established as a therapeutic option in defect reconstruction for areas without recipient vessels. Our aim was to analyse the long-term performance, flap autonomy, and the flap perfusion. Patients receiving this combined reconstruction at a single-centre institution were included. During follow-up examination, the patency of arterial reconstruction was investigated by duplex ultrasound. Flap micro-circulation was assessed by laser Doppler flowmetry and white light tissue spectrometry (O2C) as well as by indocyanine green fluorescence angiography. Twenty-three patients could be clinically followed up. Duplex ultrasound showed, in four cases, arterial pedicle occlusion in spite of vital flap. Comparison of the O2C perfusion parameters between flaps with occluded pedicles and those with intact inflow showed no significant difference (parameters sO2: P =.82; Flow: P =.31). Similar results were obtained by fluorescence angiography; no significant difference could be detected between both groups (parameters Ingress P =.13; Ingressrate P =.54). Combined vascular reconstruction with free tissue transfer is associated with a good long-term outcome and wound closure. Even after flap transplantation to areas with critical tissue perfusion, the flap can develop autonomy and thus survive after pedicle occlusion.
CRIS-Team Scopus Importer:2019-11-19
Keywords: arteriovenous loop; flap autonomy; flap perfusion; indocyanine green; laser Doppler